John Cunningham Virus seroconversion during natalizumab treatment - Vasconcelos-Pereira, Erica Freire de; Oliveira, Vanessa Marcon de; Ferreira, Cristiane Munaretto; Paula, Giovanna Arisa Tano de; Ferreira, Maria Tereza; Salgado, Pedro Rippel; Domingos, João Américo; Satomi, Massaco; Silva, Fabiany Monteiro da; Akamine, Camila Yamanaka; et al. (ABCS Health Sciences, 2024)
Introduction: Multiple sclerosis is a progressive disease that is difficult to predict, originating in cases of disability. Natalizumab is a highly effective disease-modifying therapy but is associated with greater John Cunningham virus (JCV) reactivation and consequent increased risk of developing Progressive Multifocal Leukoencephalopathy (PML). Objective: To analyze JCV seroconversion in patients treated with natalizumab. Methods: A retrospective study was conducted involving patients diagnosed with multiple sclerosis, between January 2012 and December 2021. To assess seroconversion during treatment with natalizumab, patients were considered seronegative at the beginning of treatment and who had at least one result in the period of medication use. The study was approved by the Human Research Ethics Committee under protocol 3,177,442. Results: Sixty-two patients treated with Natalizumab were included, with a seroprevalence of 67.7%. At the start of treatment, 41.9% (26/62) of the patients were negative for anti-JCV, of which 23.1% (6/26) were seroconverted. The mean time to seroconversion was 2.5 years. The baseline index of anti-JCV antibodies was statistically significant with the age of the patients. Among patients with a negative anti-JCV antibody result at baseline, 82.6% (19/23) remained negative throughout monitoring. Treatment was discontinued in 53.2% (33/62) of patients, and 72.7% (24/33) due to anti-JCV positivity with a consumption index >1.5 in 41.9% of cases. Conclusion: Knowing how to monitor the anti-JCV antibody index and treatment approaches in our patient cohort may be useful in future clinical decisions in treating MS.